CEPHALIC TETANUS: A CASE REPORT IN 68-YEAR-OLD MAN - Faraz, Ahmad; Ahmad, Nida Nousheen; Liaqat, Aimen (Journal of Ayub Medical College Abbottabad, 2016)
Cephalic tetanus is an emergency condition, which is commonly observed in child age group here we report a case of 68-year-old man with the complain of right sided weakness for one day, associated with difficulty in breathing and speech, history of fall also present, case was diagnosed as cephalic tetanus. Here we report a case of cephalic tetanus in an elderly patient. Keywords: Cephalic tetanus; Old patient; Tetanus